An activated carbon fiber cathode for the degradation of glyphosate in aqueous solutions by the Electro-Fenton mode: Optimal operational conditions and the deposition of iron on cathode on electrode reusability. (15th November 2016) - Lan, Huachun; He, Wenjing; Wang, Aimin; Liu, Ruiping; Liu, Huijuan; Qu, Jiuhui; Huang, C.P.
Abstract: An activated carbon fiber (ACF) cathode was fabricated and used to treat glyphosate containing wastewater by the Electro-Fenton (EF) process. The results showed that glyphosate was rapidly and efficiently degraded and the BOD5 /COD ratio was increased to >0.3 implying the feasibility of subsequent treatment of the treated wastewater by biological methods. The results of ion chromatography and HPLC measurements indicated that glyphosate was completely decomposed. Effective OH generation and rapid recycling/recovery of the Fe 2+ ions at the cathode were responsible primarily for the high performance of the ACF-EF process. Factors such as inlet oxygen gas flow rate, Fe 2+ dosage, initial glyphosate concentration, applied current intensity, and solution pH that may affect the efficiency of the ACF-EF process were further studied and the optimum operation condition was established. Results of SEM/EDX, BET and XPS analysis showed the deposition of highly dispersed fine Fe2 O3 particles on the ACF surface during the EF reaction. The possibility of using the Fe2 O3 -ACF as iron source in the EF process was assessed. Results showed that the Fe2 O3 -ACF electrode was effective in degrading glyphosate in the EF process. The deposition of Fe2 O3 particles on the ACF electrode had no adverse effect on the reusability of the ACF cathode. Graphical abstract: Highlights: Electro-Fenton reaction showed the highest efficiency for glyphosate degradation. Glyphosate was efficiently degraded and their intermediates are also biodegradable. The negative effect of iron deposition on ACF on EF process is not significant.